Prediction of new ZnS–CaS alloys with anomalous electronic properties. Issue 5 (11th January 2019) - Gao, Jie; Duan, Yifeng; Zhao, Changming; Liu, Wenjie; Dong, Haiming; Zhang, Dekun; Dong, Huafeng
Abstract : ZnS–CaS alloys have great potential for applications in ultraviolet optoelectronic devices due to their large and tunable band gaps. Abstract : ZnS–CaS alloys have great potential for applications in ultraviolet optoelectronic devices due to their large and tunable band gaps. However, the in-depth understanding of these sulfide compounds is hindered by the uncertainty of their phase relations and complex crystal structures. Here, we explored the new phases of a ZnS–CaS system systematically by the simulations of an ab initio evolutionary variable-composition search and the special quasirandom structures. We found three new stable phases of alloys I 4/ mcm -CaZnS2, R 3̄-Ca2 ZnS3 and R 3̄-Ca7 Zn2 S9 under pressures, which can remain dynamically and mechanically stable at ambient pressure. We found, in contrast to binary compounds, that the band structures of alloys exhibit anomalous behaviors: (I) although ZnS and CaS are wide-band-gap semiconductors, the band gaps could be tuned into the range below 2.0 eV by alloying, which is desirable for applications in solid-state lighting and high-efficient solar cells. (II) Despite the smaller band gap of CaS than that of ZnS, the band gaps of alloys are enhanced anomalously by increasing the Ca concentration due to the weak p–d repulsion between S and Zn atoms. (III) Another way to enhance the band gaps by weakening this level repulsion is by the increase of the 3d-orbital binding energy induced by pressure, which causes the band gaps to first increase and then decrease with pressure for compounds containing d-orbital electrons. Finally, we present the pressure–composition and temperature–composition phase diagrams of the alloy system, and discuss the nature of the wide and asymmetric miscibility gap, which will give a solid basis for experimental synthesis and further investigations.